Cultivation of Low-Potassium Paddy Straw Mushrooms (Volvariella volvacea) on Proline-Based Osmolyte Growing Medium to Enhance Nutritional Variety for Hyperkalemia Patients - Anisa Fatma Aulia; Dika Rohman Sholeh; Baktias Fitriani; Danawati Hari Prajitno; Rizal Arifin; Afan Hamzah (Institut Teknologi Sepuluh Nopember, 2024)
The increasing variety of food choices has led to a rise in diet-related diseases, as people often prioritize taste over nutritional content. The high consumption of sodium and potassium-rich foods has contributed to a growing number of kidney disease cases. While many studies have focused on producing low-potassium foods, these often result in suboptimal growth. Mushrooms are a nutrient-rich food source, but their high potassium content makes them unsuitable for kidney disease patients. This study aims to determine the effects of different growing media compositions and osmolyte supplementation on potassium content, yield, and mycelium growth duration in low-potassium mushrooms. The cultivation was conducted using the baglog method, starting with the preparation of a growth medium composed of a combination of sengon wood sawdust, rice bran, and dried kepok banana leaves, which were sterilized before inoculating mushroom spawn and incubated in a kumbung for 35 days. Mycelium length was observed during growth, and potassium content was tested post-harvest. The results showed that proline supplementation had an effectiveness threshold, with 3% proline in composition B yielding the best hyphae development and the highest yield of 296.67 grams with the lowest potassium content. For glycerol treatment, 5% glycerol in composition A produced the highest yield and lowest potassium content, while 1% glycerol in composition B resulted in the longest hyphae growth.